The Effectiveness of Using Pop Songs for Developing University Students' Speaking Skills - Azab, Akram Hossam Eldin Mahmoud; El-Naggar, Zeinab Ali; Yahia, Dalia Ibrahim (جامعة عين شمس - كلية التربية - الجمعية المصرية للقراءة والمعرفة, 2023)
It’s a bare fact that students these days lack enthusiasm, motivation and interest to learn English in a conventional way, this is the main reason why we as teachers should all keep an eye on the more engaging and involving activities, One of the progressive ways to bring variety into the classroom is integrating English songs in the adult EFL classes. The use of songs has a significant impact on educational settings in general and EFL in particular. Students do not find English textbooks to be particularly fascinating. It is hardly surprising that many students consider English language study as a tedious and insurmountable obstacle. In reality, English learning can be implemented in a more pleasurable and easy manner. Using pop songs in educational settings has a significant impact. Then, how might pop songs increase English language proficiency in EFL classrooms? This study will investigate the relationship between listening to English pop songs and developing speaking skills in EFL classrooms. This study will give a review of theoretical and empirical evidence on English songs and education. The study investigates the impact of employing pop songs in the EFL classroom on spoken communication skills. The outcome of the study is that English pop songs catch students' attention because they communicate English in a more natural manner than any existing textbook. Most significantly, songs serve as listening aids, enabling pupils to enhance their speaking and language skills. This study aims to develop a better understanding of the effectiveness of English pop songs as a teaching tool in EFL classrooms and to encourage language teachers to incorporate songs into their lessons. The experiment lasted six weeks, during which time the students sung sixteen popular songs. This may have influenced the results' reliability and validity. In order to obtain more accurate and valid results, sufficient time should have been allocated to the investigation. However, if a future study includes a larger number of participants and a longer time frame, it will be more generalizable to assert that popular songs may improve EFL learners' language skills, particularly their speaking.
Keywords: الوسائل التعليمية -- طرق التدريس -- تدريس اللغات -- الأغاني الشعبية -- طلبة الجامعات